A novel eight-switch nine-level modified ANPC inverter topology and its optimal modulation strategy - El-Alami, Adnane; Majdoul, Radouane; Ait Elmahjoub, Abdelhafid (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
An eight-switch nine-level modified ANPC inverter (8S-9L-MANPC) is designed and simulated in this paper. With this topology, only one DC voltage source and eight active semiconductor switches are required, significantly reducing system size, weight, and cost. The structure consists of a five-level ANPC inverter cascaded with a two-level leg converter. This arrangement extends the 5L-ANPC structure to a 9L configuration without requiring the use of additional capacitors. To maintain the balancing of the flying capacitor (FC), a modulation strategy using a switching state redundancy-based control method is employed. Recent 9L inverters incorporating flying capacitors and based on a hybrid structure have been compared with the proposed structure. By conducting this comparison, we can highlight the potential improvements offered by the proposed structure over the recent 9L inverters in terms of reduced component count, simplified design, and cost savings. The proposed 8S-9L-MANPC inverter is tested under various operating situations in MATLAB/Simulink simulation.